Influence of renal function on blood pressure control and outcome in thrombolyzed patients after acute ischemic stroke: post-hoc analysis of the ENCHANTED trial - Xinwen Ren; Xinwen Ren; Chen Chen; Chen Chen; Chen Chen; Xia Wang; Qiang Li; Yang Zhao; Yang Zhao; Shoujiang You; Menglu Ouyang; Thompson Robinson; et al. (Frontiers in Endocrinology)
BackgroundThe effect of renal impairment in patients who receive intravenous thrombolysis for acute ischemic stroke (AIS) is unclear. We aimed to determine the associations of renal impairment and clinical outcomes and any modification of the effect of intensive versus guideline-recommended blood pressure (BP) control in the BP arm of the International Enhanced Control of Hypertension and Thrombolysis Stroke Study (ENCHANTED).MethodsWe conducted a post-hoc analysis of the ENCHANTED BP arm, which involved 2,196 thrombolyzed AIS patients. Logistic regression models were used to define the association between eGFR and clinical outcomes of death, death or major disability [modified Rankin scale (mRS) scores 3–6], and major disability (mRS 3–5) at 90 days.ResultsOf the 2,151 patients with available baseline renal function data (mean age 66.9 years; 38% women), 993 (46.2%), 822 (38.2%), and 336 (15.6%) had normal (eGFR ≥ 90 mL/min/1.73 m2), mildly (60–89), and moderate-to-severely impaired (<60) renal function, respectively. Compared with patients with normal eGFR, mortality was higher in those with moderate-to-severe renal impairment (adjusted odds ratio 1.77, 95% confidence interval 1.05–2.99; p = 0.031 for trend). However, the difference in death or major disability (mRS 3–6) was not significant between groups. There was no heterogeneity in the effect of intensive versus guideline-recommended BP-lowering treatment on death by grades of renal function (p for interaction = 0.545).DiscussionThe presence of moderate-to-severe renal impairment is associated with increased mortality in thrombolyzed patients with AIS. Renal function does not modify the effect of early intensive BP-lowering treatment on death in this patient group.